Răspunsuri

2014-08-28T00:37:05+03:00

n = a×c + r1  (1)          n= (a+1)×(c-1) +r2 = a×c +c - a -1 +r2  (2)     n=(a+2)(c-2) +r3 =     a×c+2c-2a-4+r3  (3) adunam cele 3 expresii ⇒ 3n=3a×c + 3c - 3a + 23 - 5          3n=3a×c - 3a +3c +18     ⇒   n=a×c - a +c +6 ⇔a×c +c - a +(r2 - 1)  ⇒  r2-1 =6 ⇒r2 =7  ⇒    r1 + r3 =16   daca, r1 =6 si r2=10    ⇒ n =a×c + 6 si  n = a×c +2c -2a - 4 +10        ⇒ 6 = 2c - 2a + 6⇒ c=a  si n ≥ 100 ⇒a×c≥94        (n-r)   ⇒   a = c  ≥ 10   ⇒ n=106

106 = 10×10 +6       106 = 11×9 +7     106 = 12 ×8 +10




6 4 6